Chemical Composition and Antimicrobial Activity of Essential Oils from Tortella inclinata var. Densa, T. tortusa and Pleurochaete squarrosa - Tosun, Gonca; Yayli, Busra; Ozdemir, Turan; Batan, Nevzat; Yayli, Nurettin; Alpay Karaoglu, Sengul (Asian Journal of Chemistry, 2014)
Although some chemical compositional data are available about the extracts of Tortella tortusa and Pleurochaete squarrosa, there is no investigation about the compositions and antimicrobial activities of the volatiles from Tortella inclinata var. densa, Tortella tortusa and Pleurochaete squarrosa. Thus, the essential oils of these mosses were isolated by hydrodistillation and then characterised by GC-FID/MS. A total of 13, 33 and 40 compounds were identified, constituting over 93.8, 99.4 and 88.6 %, respectively. The essential oils consisted mainly of aldehydes (39.0 %, 33.2 % and 48.9 %), monoterpenes (0.0, 15.5 and 8.5 %) and hydrocarbons (48.6, 32.0 and 12.9 %). The major compound of all three essential oils was nonanal (14.8, 9.1 and 24.6 %, respectively). In addition, the antibacterial activities were investigated and the essential oils showed antimicrobial and antifungal activities against Staphylococcus aureus, Enterococcus faecalis, Bacillus cereus, Mycobacterium smegmatis, Candida albicans and Saccharomyces cerevisiae with MIC values in the range of 405-4650 μg/μL. Essential oils of all three mosses showed moderate antituberculosis activity against M. smegmatis (405-1163 μg/μL).